Comparative study of helminth parasites in Mastacembelus armatus (Lacepede, 1800) and Macrognathus pancalus (Hamilton, 1822) collected from fish market of Savar, Dhaka - Khatun, Ashura; Kamrujjaman, Md (Jahangirnagar University Journal of Biological Sciences, 2018)
Abstract not available Jahangirnagar University J. Biol. Sci. 7(1): 73-79, 2018 (June)